2015
DOI: 10.1111/jnp.12069
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term outcome of extremely preterm (<28 weeks’ gestational age) infants with and without severe retinopathy of prematurity

Abstract: Extremely preterm children with severe ROP are at increased risk for ongoing visual processing difficulties and lower IQ compared with EP peers without severe ROP. While severe ROP is a predictor of long-term impairments, this association is largely mediated by other neonatal risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 101 publications
3
36
0
Order By: Relevance
“…Developing chronic lung disease is another common condition in preterm infants, which can also impact on neurodevelopment (23). Neurodevelopment dysfunction is also increased in preterm infants who require surgery for necrotizing enterocolitis (24), who are exposed to sepsis (25), or suffer from severe retinopathy of prematurity (26). The clinical course scores were collected at discharge, following diagnosis of any of these major complications, therefore more information, comparative to the early physiological analysis, was available to accurately predict outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Developing chronic lung disease is another common condition in preterm infants, which can also impact on neurodevelopment (23). Neurodevelopment dysfunction is also increased in preterm infants who require surgery for necrotizing enterocolitis (24), who are exposed to sepsis (25), or suffer from severe retinopathy of prematurity (26). The clinical course scores were collected at discharge, following diagnosis of any of these major complications, therefore more information, comparative to the early physiological analysis, was available to accurately predict outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Ex-preterm infants also have abnormal higher visual processing that result in difficulties with visual scenes (for example, finding a toy against a patterned background), visual guidance (for example, walking over uneven ground) and recognition and orientation, all manifestations of cerebral visual impairment (Dutton, 2009, Ortibus et al, 2011 A recent study suggests that much of the demonstrable association between severe ROP and NND is the result of common shared risk factors. In a cohort of 17-18 year old former extremely low birth weight (ELBW: birth weight <1000g) infants from Victoria, Australia, Molloy and colleagues (Molloy et al, 2015) found those with a history of severe ROP had poorer test performance including on visual processing and visual-motor integration as well as reading, arithmetic and IQ compared with those without severe ROP. They also reported that after controlling for neonatal factors (severe WMI, postnatal corticosteroids and neonatal surgery) the differences between the groups diminished with only poorer visual acuity remaining significant.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Molloy et al (2015) reported that infants with severe ROP are at increased risk of poor cognitive outcome compared to very low birthweight preterm infants without eye lesions (ROP). Molloy et al (2015) reported that infants with severe ROP are at increased risk of poor cognitive outcome compared to very low birthweight preterm infants without eye lesions (ROP).…”
Section: Comparison Of Neurological Outcome To Other Collectivesmentioning
confidence: 99%
“…In this study, the most preterm children with poor neurologic outcome defined by the Bayleys scores were observed in the group of children with ROP. Molloy et al (2015) reported that infants with severe ROP are at increased risk of poor cognitive outcome compared to very low birthweight preterm infants without eye lesions (ROP). The mechanism responsible is complex and probably caused by ROP and possible accompanying processes.…”
Section: Comparison Of Neurological Outcome To Other Collectivesmentioning
confidence: 99%